Diagnostic possibilities of determination of osteogenesis disorders in children born with low body weight - Shumna, T. Ye.; Levchuk-Vorontsova, T. O. (Journal of Education, Health and Sport, 2020)
The work aims at studying the bone tissue mineral density in children born with low body weight, taking into account the dependence on the nature of feeding and polymorphism of the C/A gene polymorphism of COL1A1_1 collagen gene (rs1107946). Materials and methods. The study involved 74 children. Of these, 29 children born with the body weight of 1500-1999 g were in the observation group I; 25 children weighing 2000-2499 g - group II; 20 children with the body weight at birth of2500 g - group III (control group). All children were under inpatient treatment at the Municipal Non-Profit Enterprise "City Children Hospital no. 5" of Zaporizhia City Council. Data on the type of breastfeeding of a child aged under 1 year were analyzed for all children. The study of bone tissue mineral density was performed at the age of 12-15 months using an ultrasonic bone sonometer (densitometer) Sunlight MINIOMNI) BeamMed Ltd.,Israel. The examination was conducted at the Department of Faculty Pediatrics of theZaporizhiaStateMedicalUniversity. Analysis of the results was performed by non-parametric statistics methods using the Statistica 13 software package. Ordinal descriptive statistics was used to calculate the average Z-score indicators. The non-parametric statistical method "2 × 2 Table", the Chi-square (df = 1) was used to compare the frequencies of desitometry indicators in different groups. Results. In general, among the examined children according to densitometry data, there were no changes in the skeletal system (Z-score 0.48 ± 1.20) in 64.86% of cases, but there were osteopenia (Z-score -1.8 ± 0 , 53) in 27.03% and osteoporosis (Z-score -3.5 ± 0.96) in 8.11%. But in the further analysis by groups, the average Z-score indicator in children of the group I was 0.37 ± 2.06, in children of the group II - -0.08 ± 1.59 and in children of the group III - 0.47 ± 1, 69. But in children of the group I with body weight at birth 1500-1999g, osteopenia was registered in 34.48% of cases; the group II (2000-24999 g) - in 28.00% of cases; the group III (2500 g and more) - in 15.00% of cases. Osteoporosis was found only among children of the groups I and II. Children of the group I mainly received artificial and mixed feeding. Children of the group II received approximately the same amount of natural and artificial feeding, much less often mixed one, and 50% of children of the group III were on natural feeding. The Z-score indicators less than -1SD were found in children with AA and CA genotypes. Osteopenia was significantly less common in children with the AA genotype of the C/A gene polymorphism of COL1A1_1 collagen gene (rs1107946), who received natural or mixed feeding than in children who were exclusively on artificial feeding (p˂0.05). Among children with the AA genotype who were breastfed, there were changes in bone tissue (63.64% of children had osteopenia and 22.73% had osteoporosis). Among heterozygotes who were on artificial feeding, osteoporosis was found in 12.5%. Children with the CA genotype on mixed feeding had a decrease in bone tissue density (osteopenia) in 33.33% of cases. Children with AA genotype who were breastfed and had osteopenia, these were children weighing up to2500 g (groups I and II). Children with osteopenia on mixed breastfeeding weighed at birth up to2000 g. Osteopenia in children receiving artificial feeding was found in children of all 3 groups: 50.00% - group I, 28.57% - group II and 21, 43% - group III. Osteoporosis in breastfed children was found only among children of the groups I and II. Conclusions. According to densitometry data, among all examined children, there were no changes in the skeletal system (Z-score 0.48 ± 1.20) in 64.86%, osteopenia was registered (Z-score - 1.8 ± 0.53) in 27.03% and osteoporosis (Z-score -3.5 ± 0.96) was registered in 8.11%. But in children of the group I with body weight at birth of 1500-1999g, osteopenia was registered in 34.48% of cases; in the group II (2000-24999) in 28.00% of cases; in the group III (2500 g and more) in 15.00% of cases. Osteoporosis was found only among children born weighing up to2500 g. Children of the group I mainly received artificial (62.07%) and mixed (34.48%) feeding. Children of the group II received approximately the same amount of natural (40.00%) and artificial (44.00%) feeding, much less often mixed one. In the control group III, 50% of children were breastfed. Regardless of the type of feeding, no changes in bone tissue were detected in children with the CC genotype of the C/A gene polymorphism of COL1A1_1 collagen gene (rs1107946). The Z-scores indicators less than -1 SD were found in children with the AA and CA genotypes, and only among children with the AA genotype of polymorphism, who received natural or mixed feeding, osteopenia occurred significantly less frequently (30.00%) than among children who had exclusively artificial feeding (63.64%). Osteoporosis was detected only in children with the AA genotype (12.5%) who were on artificial feeding.